You know, sex : bodies, gender, puberty, and other things! - Silverberg, Cory (Seven Stories Press/Triangle Square Books for Young Readers, 2022)
"In a bright graphic format featuring four dynamic middle schoolers, You Know, Sex grounds sex education in social justice, covering not only the big three of puberty--hormones, reproduction, and development--but also power, pleasure, and how to be a decent human being. Centering young people's experiences of pressures and joy, risk and reward, and confusion and discovery, there are chapters on body autonomy, disclosure, stigma, harassment, pornography, trauma, masturbation, consent, boundaries and safety in our media-saturated world, puberty and reproduction that includes trans, non-binary, and intersex bodies and experience, and more. Racially and ethnically diverse, inclusive of cross-disability experience, this is a book for every kind of young person and every kind of family. You Know, Sex is the first thoroughly modern sex ed book for every body navigating puberty and adolesence, essential for kids, everyone who knows a kid, and anyone who has ever been a kid"--